The Use of Chloride, Citric and Ascorbic Acid Dip and Packaged Film to Extend the Shelf Life of Pejerrey (Odonthested bonaerensis) during Storage at Different Temperatures - Copes, Julio Alberto (2014)
The objective of this study was to analyze the effect of chloride, citric and ascorbic acid dip treatments in conjunction with two types of packaging films (with high and low gas permeability) on microbial growth in samples of pejerrey fillets (Odonthestes bonaerensis) at three storage temperatures (4˚C, 0˚C and −1.5˚C). Colour, pH, texture modification and chemical changes were also studied. Psychrotrophic microorganisms, sp. were modelled by the Gompertz’ equation. Lag phase duration, specific growth rate and maximum population density were calculated. The activation energy (Eμ) was calculated reaching values of 147 and 177 kJ/mol when the low permeability packaging films were employed. We used psychrotrophic microorganisms, sp., as a predictor of the shelf life of product. The application of treatment with chloride, citric and ascorbic acids, extended 1 - 2 days the storage life of the product (time to reach 106 CFU/g) when the packaging material used was polyethylene. The use of chloride, citric and ascorbic acids and vacuum packaging produced shelf life values of 7.7, >25 and >25 days at 4˚C, 0˚C and −1.5˚C respectively. The products had very good organoleptic characteristics, maintained their colour and texture appropriate, and absence of pathogenic microorganisms. These values indicated that the growth models were acceptable for expressing the growth of microorganisms on pejerrey fillets, which can be applied to ensure the safety of fish and to establish standards for avoiding microbial contamination.